Geographic distribution and historical occurrence of Dromiciops gliroides Thomas (Metatheria: Microbiotheria) - Martin, Gabriel Mario (2010)
Occurrence records represent the key to understanding species distribution patterns. I analyzed the historical and geographical occurrence of Dromiciops gliroides, a marsupial endemic to the temperate rain forests of southern Chile and Argentina and the sole living representative of the order Microbiotheria. Eighty-eight localities spanning 7°31′ latitude (∼850 km) and 3°13′ longitude (∼350 km) are known for the species and were taken from previous works and museum specimens and integrated in a geographic information system. Species distribution was analyzed in a historical, geographic, and biogeographic context, with the use of maps at different scales (region, subregion, province, ecoregion, and forest type). The software MaxEnt was used to generate 2 potential distribution models with environmental data. Generated models show a northern contraction and southern expansion in the species’ potential distribution, with variation in habitat suitability throughout the current species range. Precipitation and some temperature-related variables influenced both generated models. The species’ occurrence lies within the Andean region; Subantarctic and Patagonia subregions; and Maule, Valdivian, and Subandean Patagonia provinces. At a smaller scale, most of the localities occur within the Valdivian Temperate Forests ecoregion, and in the majority of the forest types described for it, implying broader ecological requirements than expected. Identification of critical areas through potential distribution modeling may have implications on species conservation and biogeographic patterns.